Dinamika Keterlibatan Orang Tua Dalam Rumah Tangga Anak: Studi Keluarga Patrilokal dan Matrilokal di Pamekasan - Ludfi, Ludfi; Fina, Ana Filstina Tahtal (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
This research aims to explore the dynamics of parental involvement in children's households in patrilocal and matrilocal families in Tattangoh Proppo Pamekasan Village with a focus on two main aspects: the typology of parental involvement and its impact on children's families, and the factors that trigger this involvement in the context local Madurese culture. This study uses a qualitative approach with a case study method, involving in-depth interviews with 10 married couples from matrilocal and patrilocal families. Researchers also use direct observation of people's involvement in children's families. The collected data was analyzed descriptively. The research results show that: First, there are two typologies of parental involvement, namely involvement in material and immaterial forms. These two typologies can have a positive impact in the form of guidance and family stability, but also have the potential to cause tension that leads to conflict, especially regarding gender roles and household autonomy, so that there is no single factor that explains the reasons for parental involvement in a child's family. Their involvement is in accordance with their customs and culture, including the teachings they follow. Second, there are three main factors that trigger parental involvement in their child's family, namely kinship, economic and spiritual (religious) strengthening factors. These findings highlight the importance of a holistic and interdisciplinary understanding to explore the complexity of parental involvement in children's families in patrilocal and matrilocal families, where local traditions and Islamic law also influence the form and intensity of this involvement. [Penelitian ini bertujuan untuk mengeksplorasi dinamika keterlibatan orang tua dalam rumah tangga anak pada keluarga patrilokal dan matrilokal di Desa Tattangoh Proppo Pamekasan dengan fokus pada dua aspek utama: tipologi keterlibatan orang tua serta dampaknya terhadap keluarga anak, dan faktor-faktor yang memicu keterlibatan tersebut dalam konteks budaya lokal Madura. Studi ini menggunakan pendekatan kualitatif dengan metode studi kasus, melibatkan wawancara mendalam terhadap 10 pasangan suami-istri dari keluarga matrilokal maupun patrilokal. Peneliti juga menggunakan observasi langsung terhadap keterlibatan orang terhadap keluarga anak. Data yang terkumpul dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa: Pertama, terdapat dua tipologi keterlibatan orang tua, yaitu keterlibatan dalam bentuk materi dan immateri. Kedua tipologi ini dapat memberikan dampak positif berupa bimbingan dan stabilitas keluarga, namun juga berpotensi menimbulkan ketegangan yang berujung pada konflik, terutama terkait peran gender dan otonomi rumah tangga, sehingga tidak ada singgle factor yang menjelaskan alasan keterlibatan orang tua dalam keluarga anak. Keterlibatan mereka sesuai dengan adat dan budaya mereka termasuk ajaran yang diikuti. Kedua, terdapat tiga faktor utama yang memicu keterlibatan orang tua terhadap keluarga anak, yaitu faktor kekerabatan, ekonomi, dan penguatan rohani (agama). Temuan ini menyoroti pentingnya pemahaman yang holistik dan lintas disiplin untuk menggali kompleksitas keterlibatan orang tua dalam keluarga anak pada keluarga patrilokal dan matrilokal, di mana tradisi lokal dan hukum Islam turut memengaruhi bentuk dan intensitas keterlibatan tersebut].